Peru : Opportunities for All, Peru Poverty Assessment - World Bank (Washington, DC, 2012)
Peru faces high levels of poverty and inequality. In 2004, over half of Peru's population was poor and about 20 percent were extremely poor. Following improvements during the 1990s, poverty increased in the wake of the 1998 economic crisis, while extreme poverty remained stable. Notwithstanding the economic recovery since 2001, with a strong positive impact in reducing extreme poverty, progress on poverty rates however, has been limited to rural areas. A main focus of this report is to explain why growth has not translated into more rapid poverty reduction. Considering the pattern of economic volatility in Peru over the past several decades - making business people reluctant to invest in job-creating endeavors, a strong reason why poverty reduction is slow. As well, in the wake of the high investment years in the 1990s followed by the 1998 crisis, many businesses have excess production capacity that is only now, after five years of growth, beginning to show fruits. This report also points to a number of obstacles that inhibit economic growth towards greater poverty reduction in Peru, and which should be addressed by government policy reforms. Growth has been focused on natural resource extraction industries, which are highly capital-intensive, and generate few jobs, and in the rural agricultural and urban informal employment sectors, which are characterized by low productivity and, therefore, low wage growth. Strengthening the linkage between growth and more, and better-paid jobs requires micro-level policy interventions to increase incentives to formal-sector employment, and diversify economic activity into more labor-intensive areas, such as non-traditional exports. While this diversification has begun - as evidenced by the rapid growth of non-traditional exports in recent years - further policy reforms can help in the process. These reforms should be accompanied by measures to boost human capital and access to public services by the poor, thereby increasing equity in economic opportunity. On socioeconomic aspects, the report further indicates social mobility, measured as the relationship between parental and children's characteristics, and proxied by education and occupational mobility, i s low and persistent in Peru. And, given that social exclusion continues to be a problem for certain groups, tackling the issue of social mobility, through the promotion of education mobility, becomes a priority.